Gas transport in aluminosilicate nanotubes by diffusion NMR - Dvoyashkin, Muslim; Wood, Ryan; Bowers, Clifford R.; Yucelen, Ipek; Nair, Sankar; Katihar, Aakanksha; Vasenkov, Sergey (Diffusion Fundamentals, 2011)
Diffusion of tetrafluoromethane in aluminosilicate nanotubes was studied by means of 13C pulsed field gradient (PFG) NMR at 297 K. The measured data allow the estimation of the diffusivity of tetrafluoromethane inside the nanotubes as well as the diffusivity for these molecules undergoing fast exchange between many nanotubes. The results support the assumption about the one-dimensional nature of the tetrafluoromethane diffusion inside nanotubes.